As águas urbanas e a problemática socioambiental no contexto escolar : o caso do Riacho do Silva em Alagoas - Salustiano, Geane Magalhães Monte (2018)
The degradation of rivers in urban centers, due to the disorderly expansion of cities associated with the patterns of society's behavior on nature, is a subject much discussed at the present time. These alterations undermine the hydrological dynamics of the watercourses that cause problems for the communities involved, such as: floods, floods and waterborne diseases during periods of rainfall. In this sense, the school plays a fundamental role in the construction of knowledge involving the local reality, especially from the development of projects as a didactic interface for teaching and learning of the socio-environmental problems of water in the urban environment. The aim of this research was to analyze the students' conceptions of the 7th year of the Alberto Torres State School about the social and environmental problems of the urban waters of Riacho do Silva, in Maceió, from an intervention project. The research was developed through the hypothetical deductive method, with applied research of a qualitative and quantitative nature and for the objectives classified as explanatory. In order to reach the proposed objectives, the following steps were carried out: bibliographical and documentary survey; planning and implementation of intervention project; application of the diagnostic questionnaire with the 40 students involved in the project; construction of Comics as a teaching didactic resource; and, organization and analysis of information. The analyzes of the study showed that the activities worked, based on curricular and interdisciplinary practices, subsidized dynamic and collaborative actions, whose knowledge was built in a shared and interactive way between teachers and students. Moreover, the results showed that there was a personal growth of the students, who became active and participative subjects of their learning and of the socio-environmental problems of the community and the creek. The activities developed in the project were important for the sensitization, participation and involvement of the students, contributing significantly to the teaching and learning process and the citizen training of the students so that they can act in their communities in the identification, analysis and resolution of problems.